Improved catalytic performance of porous metal–organic frameworks for the ring opening of styrene oxide. Issue 29 (22nd June 2017) - Julião, Diana; Barbosa, André D. S.; Peixoto, Andreia F.; Freire, Cristina; de Castro, Baltazar; S. Balula, Salete; Cunha-Silva, Luís
Abstract : An emerging strategy to improve the performance of porous metal–organic framework (MOF) materials as heterogeneous catalysts is reported. Abstract : An emerging strategy to improve the performance of porous metal–organic framework (MOF) materials as heterogeneous catalysts is reported. The incorporation of the iron-substituted polyoxometalate (POM) TBA4 [PW11 Fe(H2 O)O39 ] (PW11 Fe) in porous MOF NH2 -MIL-101(Fe), leading to a novel composite based MOF material, PW11 Fe@NH2 -MIL-101(Fe), was revealed to be a significant approach to increase the efficiency of the MOF material as a regioselective catalyst for the ring opening of styrene oxide with aniline. The conversion after 1 h of reaction using NH2 -MIL-101(Fe) is 22% and increases to 100% when PW11 Fe@NH2 -MIL-101(Fe) is employed as catalyst. It is noteworthy that the catalytic performance of this composite material is also considerably better than that obtained with the respective physical mixture under similar conditions. Furthermore, PW11 Fe@NH2 -MIL-101(Fe) revealed to be a remarkable selective heterogeneous catalyst for the studied reaction (100% selectivity to the 2-phenylamino-2-phenylethanol isomer) with significant robustness and recyclability.